The Effect of an Increased Training Volume on Oxidative Stress - Knez, W. L.; Jenkins, D. G.; Coombes, J. S. (International Journal of Sports Medicine, 2014)
This study examined the influence of training volume on resting and exercise-induced plasma markers of oxidative stress (MDA concentration) and antioxidant status (GPX, CAT & SOD erythrocyte activities). Moderately trained participants (TG) (n=6; 4 males and 2 females; 25±1.8 years) and sedentary control subjects (CG) participated in the 8-week investigation. The TG increased their training volume from ~4.9 to ~18 h.wk−1 by the end of the investigation. Before the increase in training volume and at 2-week intervals the TG completed a 30 km cycling time trial (TT30) where resting-and post-exercise blood was sampled and analysed for oxidative stress and antioxidant status. The CG had their resting blood sampled and analysed fortnightly. The data showed that TT30 performance improved in the first 4 weeks but remained unchanged in the last 4. Resting plasma MDA and CAT increased in response to training, with no change in the resting activities of erythrocyte GPX and SOD. Post-TT30 MDA and CAT increased over the training period and training hours positively related to both resting-and post-TT30 MDA. The increase in resting MDA and the up-regulation in CAT in response to an increased training volume may have a role in the identification of a training and performance plateau.
Keywords: antioxidants; malondialdehyde; lipid peroxidation; endurance training; exercise physiology